Filsafat Mistik dalam Tarekat - Armin Tedy (IAIN Bengkulu, 2022)
This paper aims to discuss various mystical philosophy concepts in tarekat. The tarekat tend to practice esoteric rituals which aim to cleanse the heart in order to draw closer to God. Congregation cannot be separated from the world of mysticism which is commonly called mysticism or in philosophy known as mystical philosophy, so it is very hot to discuss, especially when discussing the mysticism of famous Sufi figures. This research uses a literature study or research library. With some mystical philosophy Al-Ghazali his views on ma'rifah, Abu Yazid Al Busthami his views on al-fana, al-baqa and ittihad, Rabi'ah Al-Adwiyah his views on al-hubb al-ilahi/muhabbah, Al-Hallaj his views about hulul and nur muhammad